Définir la fiction climatique, ou cli-fi - Andrew Milner (ReS Futurae)
The paper begins by exploring the relationship between cli-fi and science fiction. It then proceeds to explore the history of Francophone climate fiction, from Jules Verne to Jean-Marc Ligny, through conceptualisations borrowed from utopian studies, especially the distinction between classical and critical utopias and dystopias. It argues for the importance of fictions that are scientifically plausible, but which nonetheless retain a credible utopian content and concludes by offering Kim Stanley Robinson’s The Ministry for the Future as a model of such fiction.